Anticounterfeiting method and device - MCGREW; STEPHEN P (1986)
A method of making a security device and the device are disclosed, wherein an embossable material is applied to a substrate in multiply connected regions. (A multiply connected region is one that has more than one continuous boundary). The regions have sufficient density of coverage to cause the embossable material to appear substantially continuous to the unaided eye. A diffractive pattern is embossed into a plurality of the regions and a transparent coating is applied thereover to bond firmly to the substrate and embossable material. Removal of the transparent coating results in observable damage to the security device.